Visitor monitoring in protected areas: an approach to Natura 2000 sites using Volunteered Geographic Information (VGI). Issue 1 (2nd January 2019) - Jurado Rota, Joan; Pérez Albert, María Yolanda; Serrano Giné, David
ABSTRACT: This paper analyses visitor monitoring and the public use of protected areas using volunteered geographic information (VGI) as a source of big data and, as the object of study, the Ebro Delta Natura 2000 site (west Mediterranean basin). Over 5, 000 voluntarily recorded tracks spread over 10 years have been analysed, showing a predominance of cycling activities on trails of up to 50 km in length. Using cluster analysis and a hotspot approach, we found that the highest intensities of use are concentrated in less than 1% of the area studied, while a high dispersion of track start/finish points suggests low but scattered pressure all over the site. Spatial analysis reveals a number of spatial interactions, including the use of official trails, trespassing on reserves and potential nuisance to birdlife. This information is useful for site managers and helps them design sustainable practices. By applying the same analysis using VGI and data mining to other Natura 2000 sites, comparisons can be made and thus provide valuable assessment regarding visitor monitoring and public use patterns for the largest network of protected areas in the world.